La Memoria Dictatorial en el Discurso de la Gestión Macri (Argentina, 2015-2019) - di Stefano, Mariana (Caracol, 2020)
This work analyzes, from a glotopolitical perspective, the presence of dictatorial memory in the discourse of the macrista management, in the thematic area of the so-called "internal security". The objective has been to identify the different ways through which this dictatorial memory is present and the meanings it contains. We start from the hypothesis that this memory functioned as a regulator of the construction of objects of discourse in that thematic area, as that of the "inner enemy". From a methodological point of view, given that the objective has been to test the presence of a regularity, various statements have been taken produced at different times of management by different speakers. Among the results, we have observed that dictatorial memory emerges through a discursive genre, such as the protocol of action of the security forces, and in the configuration of objects of discourse, among which we have highlighted that of "public order" and especially that of "inner enemy". In the latter, the macrist enunciation recovers the characteristic of the dictatorial formula "Marxist / Communist subversion" of accusing his enemy for the actions he carries out and for his political thinking. Keywords: glotopolitics; discursive memory; speech objects; inner enemy